2021
DOI: 10.3390/children8020077
|View full text |Cite
|
Sign up to set email alerts
|

Mealtime Environment and Control of Food Intake in Healthy Children and in Children with Gastrointestinal Diseases

Abstract: Parental feeding practices and mealtime routine significantly influence a child’s eating behavior. The aim of this study was to investigate the mealtime environment in healthy children and children with gastrointestinal diseases. We conducted a cross-sectional case–control study among 787 healthy, typically developing children and 141 children with gastrointestinal diseases, aged two to seven years. Parents were asked to provide data on demographics and describe their mealtime environment by answering to 24 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…These differences may have important implications on feeding practices of Greek parents and consequently on how they influence their children’s eating behavior. Indeed, previous research demonstrated that a large percentage of Greek parents had significant control over how much their child eats and often disregarded their child’s satiety [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences may have important implications on feeding practices of Greek parents and consequently on how they influence their children’s eating behavior. Indeed, previous research demonstrated that a large percentage of Greek parents had significant control over how much their child eats and often disregarded their child’s satiety [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same team of specialists on feeding and swallowing problems defined the features of mealtime environment to be evaluated. More information on the construction of the relevant questionnaire has already been published [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…These factors are highly significant for children with gastrointestinal diseases, who not only face the risk of developing feeding problems, but they might also be asked to strictly follow a challenging treatment comprised of limitations in diet or special diet resulting in greatly influencing child and parent feeding behavior [ 15 , 16 ]. Recent evidence supports that mealtime environment in children with gastrointestinal diseases significantly deviates from that of healthy children [ 17 ]. Parents use a significantly more often inappropriate feeding practices in these populations [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent data indicate that most children in Saudi Arabia fail to comply with dietary guidelines [ 2 ]. Even though multiple factors have been suggested to play a role in child diet quality, the current evidence points to the parental role as being a key influence [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%